Legal Politics of Implementing Public Housing Savings in Government Regulation Number 21 of 2024 based on the Siyasah Maliyah Perspective - Nadiya (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
The Tapera Programme is designed to assist Indonesians, particularly those who need financial support to purchase their first home. However, shortly after the programme’s official enactment under Government Regulation (PP) No. 21 of 2024, it faced significant public criticism. The policy was viewed as burdensome for low-income workers and unfair to middle-income earners. Despite strong opposition, the government maintained its stance, asserting that the Tapera Programme would not be delayed. This research examines three key aspects: 1) the political and legal reasoning behind the formulation of policies in PP No. 21 of 2024 concerning the Tapera Implementation Programme; 2) a comparative study of the implementation of similar housing savings programmes in other countries; and 3) an assessment of the Tapera Programme from the perspective of Siyasah Maliyah, or Islamic financial governance. Using a normative juridical research approach, the study employs both legislative and conceptual methodologies. The research reveals that the Tapera Programme is intended to support low-income communities (MBR) by easing the financial burden of home ownership through interest incentives on mortgage payments. However, the proposed implementation mechanism was unclear, and the absence of a dedicated fund management body led to concerns about potential corruption. The study also finds that, unlike in other countries where housing savings funds are voluntary and often integrated with pension schemes, Tapera contributions are mandatory, with funds restricted to housing purposes. Lastly, the Siyasah Maliyah review highlights that the programme must comply with Islamic financial principles, ensuring it provides benefits to the public while adhering to ethical financial practices, such as avoiding interest (riba). This research provides policy insights, comparative perspectives, and an evaluation of Tapera from an Islamic financial governance standpoint, offering valuable recommendations for improving the programme and ensuring its alignment with public interest and Islamic law.